Hybrid mass dampers using two types of electric servomotors AC servomotors and linear induction servomotors. - Nakamura, Y. (Earthquake engineering & structural dynamics.)
A hybrid mass damper (HMD) using an electric servomotor for vibration control of buildings has been developed. The developed HMD has been installed in three buildings in order to improve habitability during strong winds and small to moderate earthquakes. We speculated that its high performance, compactness, and high reliability are important factors in its practical application to actual buildings. We have designed and installed the HMD system with suitable specificiations for the size and demands of various object buildings. Several improvements were required for each application, e.g., the adoption of an active/passive mode switching mechanism and fault diagnosis method, countermeasures for scaling up of the devie, a linear induction servomotor, and a design controller based on the H infinity control theory. In this paper, techniques relevant to vibration control system design, an outline of applied HMD, the design of the control system, and the verified results of control performance are presented. Through several vibration tets and field observations on each building during high winds and earthquakes, the efficiency of the applied HMD system was examined and verified.